Presymptomatic spondylotic cervical cord compression - Bednařík, Josef; Kadaňka, Zdeněk; Dušek, Ladislav; Novotný, Oldřich; Šurelová, Dagmar; Urbánek, Igor; Prokeš, Boleslav (Spine, 2004)
STUDY DESIGN: We conducted a cohort study of clinically asymptomatic spondylotic cervical cord compression cases with the primary end point of the development of clinical signs of cervical myelopathy. OBJECTIVES: To investigate whether various demographic, clinical, radiologic, and electrophysiological parameters could predict progression from clinically asymptomatic (preclinical) spondylotic cervical cord compression to symptomatic myelopathy. SUMMARY OF BACKGROUND DATA: The data available on the prediction of the outcome in surgical and conservative treatment of spondylotic cervical myelopathy are controversial. Little is known about the clinical natural history of asymptomatic magnetic resonance image-detected spondylotic cervical cord compression and/or changes of signal intensity. METHODS: A group of 66 patients (32 women, 34 men, median age 50 years) with magnetic resonance signs of spondylotic cervical cord compression but without clear clinical signs of myelopathy was followed prospectively for at least 2 years (range, 2-8 years; median, 4 years). Various demographic, clinical, imaging, and electrophysiological parameters were correlated with clinical outcome. RESULTS: Clinical signs of myelopathy during the follow-up period were detected in 13 patients (19.7%). The only variables significantly associated with the development of clinically symptomatic spondylotic cervical myelopathy (SCM) were the presence of symptomatic cervical radiculopathy, electromyographic signs of anterior horn lesion, and abnormal somatosensory-evoked potentials. A multivariate logistic regression model based on these variables correctly classified 90% of cases into 2 subgroups: a group with development of symptomatic SCM and that without clinical manifestation of subclinical cervical cord compression. CONCLUSIONS: Electrophysiological abnormalities together with clinical signs of cervical radiculopathy could predict clinical manifestation of preclinical spondylotic cervical cord compression.
Keywords: dospělí; Magnetic Resonance Imaging; Anterior Horn Cells; Female; osteofytóza páteře; Adult; ženské pohlaví; komprese míchy; somatosenzorické evokované potenciály; lidé; Evoked Potentials, Somatosensory; magnetická rezonanční tomografie; krční obratle; následné studie; motorické evokované potenciály; kohortové studie; časná diagnóza; Electromyography; Cohort Studies; Evoked Potentials, Motor; prospektivní studie; Follow-Up Studies; Male; progrese nemoci; Aged; Prospective Studies; buňky předních rohů míšních; Disease Progression; Early Diagnosis; lidé středního věku; Cervical Vertebrae; Spinal Osteophytosis; senioři; mužské pohlaví; Middle Aged; Spinal Cord Compression; elektromyografie; Humans